Penerapan Prinsip Strict Liability dalam Hukum Lingkungan Internasional dan Nasional Terkait Lingkungan Laut - Fikry Latukau; Syah Awaluddin Uar (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2021)
The most crucial and widely-discussed issue is the protection of the Marine Environment Preservation. This is closely related to the survival of marine biodiversity, including its natural resources for human needs, such as fisheries. However, many human activities tend to be environmentally unfriendly, causing the marine environment polluted and damaged. The basic principles are contained in the 1969 International Convention on Civil Liability for Oil Pollution Damage, so that these principles need reviewing based on their current condition. The purpose of this research is to examine the application of the strict liability principle according to international and national law on the protection and preservation of the marine environment. As the principle excepting Chapter XII on the Protection and Preservation, the 1982 Law of the Sea Convention is not only restricted to cases of oil spills, which is the 1969 international convention Article 3 paragraph (1) as the legal basis. However, the Caledonian sky case having an impact on the threat of the marine environment like damaged and threatened coral reefs, confirm a legal vacuum related to international conventions that regulate the strict liability principle in the context of pollution and environmental damage.